2017
DOI: 10.1142/s0129055x17500088
|View full text |Cite
|
Sign up to set email alerts
|

Quantum isometry groups of dual of finitely generated discrete groups and quantum groups

Abstract: We study quantum isometry groups, denoted by Q(Γ, S), of spectral triples on C * r (Γ) for a finitely generated discrete group Γ coming from the word-length metric with respect to a symmetric generating set S. We first prove a few general results about Q(Γ, S) including:• For a group Γ with polynomial growth property, the dual of Q(Γ, S) has polynomial growth property provided the action of Q(Γ, S) on C * r (Γ) has full spectrum. • Q(Γ, S) ∼ = QISO(Γ, d) for any discrete abelian group Γ, where d is a suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Note that the above quantum groups appeared as quantum isometry groups of the free products of finite cyclic groups in [4] and [14]. There is also a classical version of this result.…”
Section: Definition 54 An Action α : Gmentioning
confidence: 78%
“…Note that the above quantum groups appeared as quantum isometry groups of the free products of finite cyclic groups in [4] and [14]. There is also a classical version of this result.…”
Section: Definition 54 An Action α : Gmentioning
confidence: 78%
“…
In this article we have shown that the quantum isometry group of C * r (Z), denoted by Q(Z, S) as in [16], with respect to a symmetric generating set S does not depend on the generating set S. Moreover, we have proved that the result is no longer true if the group Z is replaced by Z × Z × · · · × Z n copies for n > 1.
…”
mentioning
confidence: 94%
“…Consider the generating sets S 1 = {(1, 0), (0, 1), (−1, 0), (0, −1)} and S 2 = {(1, 1), (−1, −1)} respectively for Z n ×Z 4 . The underlying C * -algebra of Q(Z n ×Z 4 , S 1 ) is noncommutative by Theorem 4.10 of [16]. On the other hand, Q(Z n × Z 4 , S 2 ) is the doubling of C * (Z n × Z 4 ) corresponding to the automorphism given by a → a −1 ∀ a ∈ Z n × Z 4 from [8].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several articles already on computations and study of the quantum isometry groups of such spectral triples, e.g [11], [23], [16], [6], [4] and references therein. In [19] together with Goswami we also studied the quantum isometry groups of such spectral triples in a systematic and unified way. Here we compute Q(Γ, S) for more examples of groups including braid groups, Z 4 * Z 4 · · · * Z 4 n copies etc.…”
Section: Introductionmentioning
confidence: 99%
“…
As a continuation of the programme of [19], we carry out explicit computations of Q(Γ, S), the quantum isometry group of the canonical spectral triple on C * r (Γ) coming from the word length function corresponding to a finite generating set S, for several interesting examples of Γ not covered by the previous work [19]. These include the braid group of 3 generators, Z * n 4 etc.
…”
mentioning
confidence: 99%